2016
DOI: 10.1002/jor.23340
|View full text |Cite
|
Sign up to set email alerts
|

Controlled laser texturing of titanium results in reliable osteointegration

Abstract: We have developed a laser-textured superhydrophilic Ti-6Al-4V surface with unique surface chemistry and topography that substantially promotes osteoblast adhesion in culture. Here we investigate the osteointegration of laser-textured implants in an ovine model. Our hypothesis was that laser-textured implants, without any surface coating (LT), would encourage comparable amounts of bone-implant contact and interfacial strength when compared with widely accepted hydroxyapatite (HA) coated implants. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 41 publications
1
41
0
1
Order By: Relevance
“…Stanje površine implanata značajno određuje inicijalna faza biološke reakcija tokom njihovog ugrađivanja i utiče na proces njihovog koštanog zarastanja 1 . Utvrđeno je da rast i diferencijacija osteoblasta zavise direktno od mikrostrukture implanata: hrapava površina može da ubrza process osteointegracije i poveća procenat preživljavanja implanata 2,3 . Međutim, sa početkom nošenja protetskih nadoknada na dentalnim implantima, javlja se rizik od periimplantitisa -akutne i hronične inflamacije tkiva koje okružuje implant 1,4,5 .…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Stanje površine implanata značajno određuje inicijalna faza biološke reakcija tokom njihovog ugrađivanja i utiče na proces njihovog koštanog zarastanja 1 . Utvrđeno je da rast i diferencijacija osteoblasta zavise direktno od mikrostrukture implanata: hrapava površina može da ubrza process osteointegracije i poveća procenat preživljavanja implanata 2,3 . Međutim, sa početkom nošenja protetskih nadoknada na dentalnim implantima, javlja se rizik od periimplantitisa -akutne i hronične inflamacije tkiva koje okružuje implant 1,4,5 .…”
Section: Uvodunclassified
“…The condition of the implant surface significantly determines the initial phase of biological reactions during its installation and affects the boneimplant healing process 1 . It was found that the growth of osteoblasts and their differentiation on the implant surface directly depends on implant's microstructure: a rough surface can accelerate the process of osteointegration and thereby increase survival rate 2,3 . However, after the patient began using orthopedic constructions based on dental implants, there is a risk of periimplantitis: acute and chronic inflam-mation in the area of the tissues surrounding an implant1 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the stoichiometric defects and the low stability of this film can lead, in the case of implants, to their delamination and loosening. The key parameter in the success of bone implants (orthopaedics and dentistry) and the clinical goal is the establishment of a strong and long-lasting connection between the implant surface and peri-implant bone, in other word, achieving the optimal osseointegration [38][39][40][41][42][43]. Even if Ti and its alloys are biocompatible materials, as they are biostable and biologically inert, the human body recognizes them as foreign ones and tries to isolate them using thin nonmineral, soft tissue layer.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple techniques have been proposed to increase osteointegration in metals. Probably the most accepted and used are the creation of a plasma coating with hydroxyapatite in some situations and the texturization of the metal in the microscale [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Laser processing has gained significant importance in the medical industry and is an integral part of manufacturing, for example, welding endoscopes, drilling holes in hypodermic needles and verification laser marking [2,3]. Lasers offer high precision and repeatability, high speed and quality, accuracy, cost efficiency, minimal thermal input and noncontact [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%